Fiber reinforced resin matrix composite material with damping impact resistance performance and its preparation method and application
Patent Information
- Application Number
- CN202611031144.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2046-07-13
AI Technical Summary
该方法制备的预浸料同样存在一些不足之处,主要包括:有大量研究已经表明碳纳米管与环氧树脂基体之间的界面结合力较弱,这也限制了复合材料性能的充分发挥
(1)本发明在复合材料层间添加一种具有高阻尼性能的杂化颗粒,其核心意义在于构建了一种新型的“协同耗能体系”。通过将一维纳米芳纶纤维、减振橡胶颗粒与高比表面积一维碳纳米管化学/物理作用耦合,制得高阻尼性能的“项链式”杂化颗粒。
Smart Images

Figure CN122518747B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber-reinforced composite materials technology, specifically to a fiber-reinforced resin-based composite material with damping and impact-resistant properties, its preparation method, and its applications. Background Technology
[0002] Carbon fiber reinforced resin matrix composites (CFRPs), with their ultra-high specific strength, specific modulus, and excellent corrosion resistance, have become a material widely used in modern industry, especially in high-end manufacturing. Driven by the pursuit of lightweighting and high reliability, CFRPs are extensively applied to long blades of wind turbines, fuselage skins of aircraft, and critical wing components. However, carbon fiber composites face two significant technical bottlenecks in actual service: insufficient damping performance and relatively weak impact resistance.
[0003] For the wind power industry, as blade lengths have exceeded 100 meters, the rigidity of the blades has increased dramatically, but their internal energy dissipation capacity (damping) has lagged behind. Under alternating wind loads, blades are prone to severe vibrations. Long-term accumulation of vibration energy can induce structural fatigue failure and shorten the service life of the transmission system. Traditional toughening and vibration reduction methods typically involve adding thick rubber pads or damping layers between the layers, but this often comes at the cost of sacrificing the overall stiffness and load-bearing capacity of the composite material, and the increased thickness significantly increases the blade's weight. Therefore, how to improve the blade's inherent damping performance without reducing its mechanical strength is a key challenge currently facing the wind power industry.
[0004] Furthermore, in the aerospace field, composite material skins are frequently threatened by low-velocity impacts, such as hailstorms and dropped tools. Due to their brittle nature, carbon fiber composites are highly susceptible to interlaminar delamination upon impact. This damage often occurs within the material and is difficult to detect with the naked eye, yet it significantly reduces the structure's residual compressive strength.
[0005] Existing nanomaterial modification techniques (such as directly adding carbon nanotubes or graphene to resins) can improve performance to some extent, but due to the extremely high specific surface area of nanomaterials, they are prone to agglomeration in viscous resins. This not only fails to utilize the performance of nanomaterials but also creates stress concentration points, leading to a deterioration of the most important interfacial properties of composite materials, and consequently, a decline in the mechanical properties of structural components. For example: CN202510932652.7 discloses a carbon fiber composite material with both interfacial and damping properties, and its preparation method. The material comprises the following percentage components: 65-75% carbon fiber, 25-35% modified butyl rubber resin matrix, 0.5-2% butyl rubber film, 0.5-1% polyurethane-based sizing agent, and 0.1-0.5% silane coupling agent. While this carbon fiber composite material possesses certain interfacial and damping properties, this method is only applicable to resin property modification and suffers from significant problems in achieving uniform dispersion of rubber particles.
[0006] CN202211028749.8 discloses a carbon nanotube-reinforced co-cured damping composite material and its preparation method, comprising the following steps: (1) growing carbon nanotubes on the surface of carbon fibers, combining the carbon fibers with grown carbon nanotubes with epoxy resin to prepare carbon nanotube-modified epoxy resin-based carbon fiber prepreg, and laying the epoxy resin-based carbon fiber prepregs with different carbon nanotube contents in a gradient order to form a composite material preform with functional gradient distribution; (2) plasticizing and mixing the cut hydrogenated carboxylated nitrile rubber to obtain a uniformly mixed raw rubber; (3) dissolving the uniformly mixed raw rubber in an easily volatile organic solvent to form a slurry, uniformly coating the slurry onto a substrate to form a viscoelastic damping film; (4) embedding the viscoelastic damping film as an intermediate layer between two composite material preforms through a co-curing process in an autoclave. This method still has some shortcomings, mainly including: low efficiency of carbon nanotube growth on carbon fiber surface, difficulty in controlling the uniformity and height of carbon nanotube growth, and difficulty in achieving high-volume carbon fiber surface modification; in addition, the pretreatment and chemical modification process of carbon fiber during carbon nanotube growth undoubtedly damages the strength of carbon fiber, so this method needs further improvement and optimization.
[0007] CN202010019642.1 discloses an aramid fiber / carbon nanotube composite reinforced carbon fiber resin prepreg, the mass ratio of its raw material components is: 100 parts epoxy resin, 0.25~2 parts carbon nanotube, 0.25~2 parts aramid fiber, and 67~400 parts carbon fiber. The specific steps of its preparation method are as follows: (1) Place the aramid fiber and CNT in a forced-air drying oven to dry them thoroughly and remove the internal adsorbed moisture; (2) Mix 10 wt% of epoxy resin component A with an equal amount of acetone, and add CNT gradually in multiple batches while stirring continuously until epoxy resin component A is completely dissolved and CNT is evenly dispersed; the epoxy resin is divided into two parts: component A is the resin part and component B is the curing agent part, only component A is used here; (3) Add the mixed solution of epoxy resin component A, acetone and CNT to the aramid fiber, stir thoroughly and evenly so that the solution fully wets and coats the aramid fiber; (4) Place the mixture in a forced-air drying oven and dry at 90°C. Heat treatment at ℃ until acetone completely evaporates; (5) Add the remaining 90 wt% of epoxy resin component A to the above mixture in multiple portions, while continuously stirring for more than 12 hours until aramid fibers and CNTs are uniformly dispersed in epoxy resin component A; (6) Add epoxy resin component B according to the proportion, and mix and homogenize using a three-roll mill; (7) Prepare an aramid fiber / CNT composite epoxy resin film by coating, hot pressing, and cooling on a coating machine; (8) Use a prepreg machine to combine the pre-made aramid fiber / CNT composite epoxy resin film with carbon fiber, and prepare an aramid fiber / CNT composite reinforced carbon fiber resin prepreg through a coating and curling process. The prepreg prepared by this method also has some shortcomings, mainly including: a large number of studies have shown that the interfacial bonding force between carbon nanotubes and epoxy resin matrix is weak, which also limits the full development of the composite material performance. This method mixes carbon nanotubes with epoxy resin, which undoubtedly causes the carbon nanotubes to agglomerate under the action of van der Waals forces. Moreover, the method is too rough, and the high concentration of carbon nanotubes will cause the viscosity of epoxy resin to increase, which will seriously affect the full impregnation of aramid fibers. Summary of the Invention
[0008] To address the aforementioned problems in the prior art, the present invention aims to provide a fiber-reinforced resin matrix composite material with damping and impact-resistant properties, its preparation method, and its applications. The present invention utilizes specific chemical methods and physical processes to prepare a hybrid particle with high damping performance, which is then introduced into the interlayer interface of a carbon fiber composite material, thereby obtaining a fiber-reinforced resin matrix composite material with damping and impact-resistant properties.
[0009] Specifically, the present invention provides the following technical solution: A method for preparing a fiber-reinforced resin-based composite material with damping and impact-resistant properties is as follows: First, carbon nanotubes (CNTs) are embedded into rubber particles (R) under high-speed shear force through ball milling, unlike simple lamination, forming hybrid carbon nanotube-co-embedded rubber particles (RC). Then, the RC particles are anchored onto high aspect ratio nano-aramid fibers (ANFs) through an aramid fiber deprotonation process, constructing ARC hybrid vibration-damping particles with a "necklace" structure. Finally, the ARC particles are uniformly distributed on the surface of a fiber prepreg using a spraying process, and the composite material is obtained by hot pressing. The technical principle is as follows: (1) Construction mechanism of hybrid particles with high damping performance: First, high-energy ball milling is used to tightly wrap and encapsulate carbon nanotubes (CNTs) onto the surface of elastic rubber particles (R) under mechanical force, forming hybrid carbon nanotube-co-embedded rubber particles (RC). Subsequently, a solution of nanoscale aramid fibers (ANFs) is exfoliated by the deprotonation reaction of aramid fibers in a strongly alkaline dimethyl sulfoxide / potassium hydroxide system (reference method: CN201910340388.2 A method for preparing aramid nanofibers). In this process, after the RC units are introduced into the ANFs solution, the RC particles are anchored along the long chain direction of the ANFs fibers, forming a hybrid structure similar to a pearl "necklace." ANFs provide effective spatial support for the RC units, preventing secondary aggregation and dispersibility in the solvent and resin matrix.
[0010] (2) Vibration reduction performance: When the composite material is subjected to vibration or impact, the "necklace" structure of this ARC hybrid damping particle dissipates energy through three pathways: first, the viscoelastic hysteresis deformation of the rubber particles themselves; second, the huge interfacial friction between the high specific surface area carbon nanotubes and the resin and ANFs; and third, the bridging and pull-out effect of the ANFs network during microcrack propagation.
[0011] Specifically, the following steps are included: (1) Rubber particles, carbon nanotubes, surfactants, modifiers and solvents are mixed and ball milled to obtain mixed carbon nanotubes co-embedded rubber particles; (2) Aramid fibers are dissolved in a deprotonation system to obtain an aramid nanofiber solution. The mixed carbon nanotubes co-embedded rubber particles prepared in step (1) are added. Through solvent exfoliation and adsorption, a high-damping hybrid particle solution with a "necklace" structure is constructed. The solvent is anhydrous ethanol or methanol and other volatile solvents. (3) The high-damping hybrid particle solution is prepared into a spraying liquid and uniformly sprayed onto the surface of the fiber prepreg; (4) The sprayed fiber prepreg is laid up and then the fiber-reinforced resin matrix composite material with damping and vibration reduction properties is obtained by hot pressing molding process.
[0012] Furthermore, in step (1), the mass ratio of rubber particles to carbon nanotubes is 1:(2~4); the surfactant is sodium dodecyl sulfate, and the modifier is any one of silane coupling agents KH550, KH560, and KH570.
[0013] Furthermore, in step (1), the ball milling speed is 300~500 r / min, the ball milling time is 12-36 h, and the solvent is a mixed solution of ethanol and water.
[0014] Furthermore, in step (2), the mass ratio of aramid fiber to mixed carbon nanotube co-embedded rubber particles is 1:(4~6); the deprotonation system is a mixture of dimethyl sulfoxide and potassium hydroxide.
[0015] Furthermore, in step (3), the mass fraction of the high-damping hybrid particles in the spraying liquid is 0.3 wt%~0.8 wt%, and the solvent is anhydrous ethanol or methanol.
[0016] Furthermore, in step (3), the spraying pressure is 0.2~0.4 MPa, and the spraying distance is 15~35 cm; the loading of high-damping hybrid particles on the prepreg surface is controlled at 0.25~2.5 mg / cm by controlling the spraying time. 2 .
[0017] Furthermore, in step (4), the hot pressing temperature is 130~250 ℃, the pressure is 0.3~0.7 MPa, and the constant temperature and pressure time is 1~2 h; the fiber prepreg is a resin-based prepreg made of long fibers, and the long fibers include at least one of carbon fiber, glass fiber, aramid fiber, and hybrid fiber, and the fiber direction is not limited, nor is the layup direction limited.
[0018] Furthermore, the fiber prepreg is a carbon fiber reinforced epoxy resin prepreg, wherein the fiber also includes at least one of glass fiber, aramid fiber, and hybrid fiber; the layup method is any one of symmetrical layup, unidirectional layup, and orthogonal layup.
[0019] The fiber-reinforced resin matrix composite material obtained by this invention can be used in fields with stringent requirements for vibration suppression, such as wind turbine blades, aerospace skins, or transportation structural components.
[0020] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention adds a hybrid particle with high damping performance between the composite material layers. Its core significance lies in constructing a new type of "synergistic energy dissipation system". By coupling one-dimensional nano-aramid fiber, vibration damping rubber particles and one-dimensional carbon nanotubes with high specific surface area through chemical / physical interaction, a "necklace-like" hybrid particle with high damping performance is prepared.
[0021] (2) Aramid nanofibers have an extremely high aspect ratio and excellent mechanical skeleton effect. Like a rope, they connect rubber particles with high damping characteristics with carbon nanotubes with high specific surface area enhancement to form a "necklace" structure. This structure solves the problem of easy agglomeration and difficulty in dispersion of nanomaterials in resin or on the surface of prepreg, and achieves uniform distribution of functional particles with extremely low loading through spraying.
[0022] (3) This invention not only provides a new idea for solving the contradiction of the incompatibility between "high strength and high damping" of CFRP, but also opens up a new technical path for the fatigue and impact resistance design of wind turbine blades and aerospace structural components. Attached Figure Description
[0023] Figure 1 A schematic diagram of the process for preparing highly damped hybrid particles.
[0024] Figure 2 SEM image of the ARC hybrid vibration damping material prepared in step (2) of Example 1.
[0025] Figure 3 This is a comparison chart of damping performance.
[0026] Figure 4 This is a diagram showing the glass transition temperatures.
[0027] Figure 5 The image shows the comparison results of impact performance.
[0028] Figure 6 The image shows the vibration test results for a single cantilever beam.
[0029] Figure 7 This is a schematic diagram of a single cantilever beam vibration test experiment.
[0030] Figure 8 This is a photograph of a vibration test experiment on a single cantilever beam. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Combination Figure 1 As shown, the preparation process of the high-damping impact-resistant carbon fiber composite material of the present invention is as follows: (1) Preparation of RC particles (mixed carbon nanotube co-embedded rubber particles): R rubber particles and CNTs were ball-milled and mixed at a certain mass ratio. At the same time, 2 wt% sodium dodecyl sulfate (SDS surfactant), 5 wt% KH550 (modifier) and ethanol / water mixed solvent (volume ratio 1:1) were added. After ball milling for several hours, the particles were washed several times with ethanol and deionized water to remove impurities. The particles were dried and ground to obtain mixed particles (RC) for later use.
[0033] (2) Preparation of ARC solution (high-damping hybrid particle solution): Aramid fibers and RC particles were dispersed in a mixture of dimethyl sulfoxide and potassium hydroxide (dimethyl sulfoxide to potassium hydroxide mass ratio of 100:1) at a certain mass ratio and stirred in a water bath for 4 h. Then, a certain amount of deionized water (4 times the mass of dimethyl sulfoxide) was slowly added and stirred for several hours. This process mainly promotes the deprotonation of aramid fibers to form nanoscale ANFs. During the deprotonation process, RC particles adhere to the surface of ANF nanofibers. Finally, the mixture was washed three times with deionized water and twice with ethanol to obtain an ethanol solution of ARC hybrid particles of a certain concentration (ethanol solution is more volatile during spraying). Since the surface of ANFs contains a large number of hydrophilic functional groups, it can be stably dispersed in the ethanol solution.
[0034] (3) Spraying process on carbon fiber prepreg: The diluted ARC solution is uniformly covered on the surface of carbon fiber prepreg by micro-atomization spraying process. A hot air blower can be used to facilitate the evaporation of solvent ethanol and form an extremely thin and uniform ARC nano-functional network on the surface of carbon fiber prepreg.
[0035] (4) Carbon fiber composite material molding process: prepregs are stacked according to the designed layup sequence and cured using a hot autoclave or flat plate hot press to finally obtain carbon fiber resin-based composite material with high damping and impact resistance.
[0036] Comparative Example The carbon fiber prepreg was laid up in 8 symmetrical (0 / 90°) layers and hot-pressed at 150 ℃ and 0.5 MPa for 1.5 h to finally form a carbon fiber composite plate (CFRP).
[0037] Example 1
[0038] (1) Using an R:CNT mass ratio of 1:3, 2 wt% SDS, 5 wt% KH550, and an ethanol / water mixed solvent were added. The ball milling speed was 400 r / min and the time was 4 h. After ball milling, the mixture was washed twice with ethanol and twice with deionized water, and then dried and ground to obtain mixed particles (RC).
[0039] (2) Aramid fibers and RC mixed particles were mixed at a ratio of 1:5, and the reaction was carried out with dimethyl sulfoxide / potassium hydroxide solution as solvent for 12 h. Then, the mixture was washed three times with deionized water and twice with ethanol by filtration to form ARC particles. Finally, the concentration of ARC was adjusted to form an ARC particle / ethanol solution.
[0040] (3) Prepare an ARC ethanol spraying solution with a concentration of 0.5 wt%. Under the conditions of a distance of 20 cm and a pressure of 0.2 ~ 0.4 MPa, spray using an Ihara-W101 spray gun, with the assistance of a hot air gun. The spraying amount on the surface of the carbon fiber prepreg is controlled to be 0.5 mg / cm. 2 .
[0041] (4) The carbon fiber prepreg is laid up in 8 symmetrical (0 / 90°) layers (i.e., arranged in the order of layer 1 0°, layer 2 90°, layer 3 0°, layer 4 90°...). It is hot-pressed at 150 ℃ and 0.5 MPa for 1.5 h to finally form a carbon fiber composite board CFRP-0.5 with high damping and impact resistance. The damping and vibration reduction performance and impact resistance performance are both good.
[0042] Example 2
[0043] (1) Using an R:CNT mass ratio of 1:3, 2 wt% SDS, 5 wt% KH550, and an ethanol / water mixed solvent were added. The ball milling speed was 400 r / min and the time was 4 h. After ball milling, the mixture was washed twice with ethanol and twice with deionized water, and then dried and ground to obtain mixed particles (RC).
[0044] (2) Aramid fibers and RC mixed particles were mixed at a ratio of 1:5, and the reaction was carried out with dimethyl sulfoxide / potassium hydroxide solution as solvent for 12 h. Then, the mixture was washed three times with deionized water and twice with ethanol by vacuum filtration to form ARC particles. The concentration of ARC was then adjusted to form an ARC particle / ethanol solution.
[0045] (3) Prepare an ARC ethanol spraying solution with a concentration of 0.25 wt%. Under the conditions of a distance of 20 cm and a pressure of 0.2 ~ 0.4 MPa, spray the solution using an Ihara-W101 spray gun, with the assistance of a hot air gun, to control the spraying amount on the surface of the carbon fiber prepreg to 0.25 mg / cm. 2 .
[0046] (4) The carbon fiber prepreg is laid up in 8 symmetrical (0 / 90°) layers and hot-pressed at 150 ℃ and 0.5 MPa for 1.5h to finally form a carbon fiber composite board CFRP-0.25 with high damping and impact resistance.
[0047] At this addition amount, the concentration of ARC mixed vibration damping particles is low, the dispersion is uneven, and the overall performance is poor.
[0048] Example 3
[0049] (1) Using an R:CNT mass ratio of 1:3, 2 wt% SDS, 5 wt% KH550, and an ethanol / water mixed solvent were added. The ball milling speed was 400 r / min and the time was 4 h. After ball milling, the mixture was washed twice with ethanol and twice with deionized water, and then dried and ground to obtain mixed particles (RC).
[0050] (2) Aramid fiber and RC mixed particles were mixed in a ratio of 1:5. Dimethyl sulfoxide / potassium hydroxide solution was used as solvent and the mixture was stirred for 12 h. Then, the mixture was washed three times with deionized water and twice with ethanol by filtration. The concentration of ARC was adjusted to form ARC particles / ethanol solution.
[0051] (3) The 1 wt% ARC ethanol spraying solution was prepared and sprayed using an Ihara-W101 spray gun at a distance of 20 cm and a pressure of 0.2 ~ 0.4 MPa, with the assistance of a hot air gun, to control the spraying amount on the surface of the carbon fiber prepreg to 1 mg / cm. 2 .
[0052] (4) The carbon fiber prepreg is laid up in 8 symmetrical (0 / 90°) layers and hot-pressed at 150 ℃ and 0.5 MPa for 1.5h to finally form a carbon fiber composite board CFRP-1 with high damping and impact resistance.
[0053] At this addition amount, excessive ARC mixed vibration damping particles and excessively thick spray coating will cause agglomeration between composite material layers, making it difficult to effectively utilize the three-dimensional network vibration energy dissipation of one-dimensional ANFs nanofibers, high specific surface area CNTs, and high damping rubber particles, resulting in poor overall performance and similarly poor impact resistance of the composite plate.
[0054] Example 4
[0055] (1) Using an R:CNT mass ratio of 1:3, 2 wt% SDS, 5 wt% KH550, and an ethanol / water mixed solvent were added. The ball milling speed was 400 r / min and the time was 4 h. After ball milling, the mixture was washed twice with ethanol and twice with deionized water, and then dried and ground to obtain mixed particles (RC).
[0056] (2) Aramid fibers and RC mixed particles were mixed at a ratio of 1:5, and the reaction was carried out with dimethyl sulfoxide / potassium hydroxide solution as solvent for 12 h. Then, the mixture was washed three times with deionized water and twice with ethanol by vacuum filtration to form ARC particles. The concentration of ARC was then adjusted to form an ARC particle / ethanol solution.
[0057] (3) Using ARC ethanol spraying solution with a concentration of 0.75 wt%, at a distance of 20 cm and a pressure of 0.2 ~ 0.4 MPa, spraying was performed using an Ihara-W101 spray gun, with the assistance of a hot air gun, to control the spraying amount on the surface of the carbon fiber prepreg to be 0.75 mg / cm. 2 .
[0058] (4) The carbon fiber prepreg is laid up in 8 symmetrical (0 / 90°) layers and hot-pressed at 150 ℃ and 0.5 MPa for 1.5h to finally form a carbon fiber composite board CFRP-0.75 with high damping and impact resistance.
[0059] At this addition amount, the ARC mixed vibration damping particles can effectively exert vibration damping performance. Its damping performance is slightly less than 0.5wt%, but it can still exert good damping vibration damping performance.
[0060] Example 5
[0061] The basic parameters are the same as in Example 1, except that the hot-pressing temperature is adjusted to 180°C and the pressure is increased to 0.7 MPa. The penetration and fusion of the interlayer ARC particles and the resin matrix are observed by increasing the pressure.
[0062] Using 0.5 wt% ARC as a reference, the hot pressing temperature of the composite material was adjusted according to the hot pressing process of commercial prepreg (the hot pressing temperature was adjusted to 180℃ and the pressure was increased to 0.7 MPa) to explore the effect of hot pressing temperature on the hybrid vibration damping particles and the comprehensive performance of the composite material.
[0063] (1) Using an R:CNT mass ratio of 1:3, 2 wt% SDS, 5 wt% KH550, and an ethanol / water mixed solvent were added. The ball milling speed was 400 r / min and the time was 4 h. After ball milling, the mixture was washed twice with ethanol and twice with deionized water, and then dried and ground to obtain mixed particles (RC).
[0064] (2) Aramid fibers and RC mixed particles were mixed in a ratio of 1:5, and dimethyl sulfoxide / potassium hydroxide solution was used as solvent. The mixture was stirred for 12 h, and then washed three times with deionized water and twice with ethanol by filtration to form ARC hybrid damping particles.
[0065] (3) Prepare an ARC hybrid particle / ethanol spraying solution with a concentration of 0.5 wt%. Apply the solution using an Ihara-W101 spray gun at a distance of 20 cm and a pressure of 0.2 ~ 0.4 MPa, with the assistance of a hot air gun. Control the spraying amount on the carbon fiber prepreg surface to be 0.5 mg / cm. 2 .
[0066] (4) The carbon fiber prepreg is laid in 8 symmetrical (0 / 90°) layers and hot-pressed at 180 ℃ and 0.7 MPa for 1.5 h. Finally, the carbon fiber composite board CFRP-0.5 is formed. Its appearance morphology does not change. Therefore, in actual use, it is only necessary to cure according to the curing process recommended for the prepreg. It is not related to ARC mixed particles and has good commercial applicability.
[0067] Performance testing The performance of the samples prepared in the comparative examples and embodiments described above was characterized, and the results are as follows: (1) Damping performance test (results are as follows) Figure 3-4 (As shown), refer to GB / T 18258 (Damping Material Performance Test).
[0068] In the constant frequency temperature sweep mode, the loss factor performance comparison in the examples shows that the damping performance of the composite material with added ARC hybrid damping particles changes significantly, and the glass transition temperature is moved forward, exhibiting a better damping effect. Therefore, ARC hybrid particles can play a good damping role.
[0069] (2) Impact resistance (drop hammer impact, results as follows) Figure 5 (As shown), refer to GB / T 14153-1993 (Rigid Plastics Drop Impact Test).
[0070] Examples 1-4 illustrate the impact performance changes of the composite materials under a 10 J energy impact. The composite material with 0.5 wt% ARC damping particles exhibits significantly better damping performance and a greater impact load. Furthermore, the impact resistance of the composite material decreases when the addition amount exceeds 0.5 wt%, primarily because excessive ARC affects the resin flow and crosslinking between the composite layers.
[0071] (3) Vibration reduction performance (cantilever beam test, results are as follows) Figure 6 As shown, the experimental schematic diagram and physical diagram are as follows. Figure 7-8 As shown), the experiment was conducted in accordance with the reference (Wang Liang, Chen Huaihai, He Xudong, et al. Damping and boundary condition test of axial motion cantilever beam system, 2010, 30(5), 547-551).
[0072] The vibration decay time of Example 1 was shortened by more than 60% compared to the pure composite material group. The acceleration-time curve showed a very large amplitude decay slope, verifying the effectiveness of ARC hybrid particles in vibration reduction of macroscopic composite structures.
[0073] (4) Morphology of ARC mixed particles RC particles adhere to the surface of ANF fibers, forming a uniformly dispersed three-dimensional damping structure. The SEM image of the ARC hybrid damping material in step (2) of Example 1 is shown below. Figure 2 As shown.
[0074] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing a fiber-reinforced resin-based composite material with damping and impact-resistant properties, characterized in that, Includes the following steps: (1) Rubber particles, carbon nanotubes, surfactants, modifiers and solvents are mixed and ball milled to obtain mixed carbon nanotubes co-embedded rubber particles; (2) Aramid fibers are dissolved in a deprotonation system to obtain an aramid nanofiber solution. The mixed carbon nanotubes co-embedded rubber particles prepared in step (1) are added. Through solvent exfoliation and adsorption, a high-damping hybrid particle solution with a "necklace" structure is constructed. (3) The high-damping hybrid particle solution is prepared into a spraying liquid and uniformly sprayed onto the surface of the fiber prepreg; (4) The sprayed fiber prepreg is laid up and then the fiber-reinforced resin matrix composite material with damping and vibration reduction properties is obtained by hot pressing molding process.
2. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (1), the mass ratio of rubber particles to carbon nanotubes is 1:(2~4); the surfactant is sodium dodecyl sulfate, and the modifier is any one of silane coupling agents KH550, KH560, and KH570.
3. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (1), the ball milling speed is 300~500 r / min and the ball milling time is 12-36 h; the solvent is a mixed solution of ethanol and water.
4. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (2), the mass ratio of aramid fiber to mixed carbon nanotube co-embedded rubber particles is 1:(4~6); the deprotonation system is a mixture of dimethyl sulfoxide and potassium hydroxide.
5. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (3), the mass fraction of the high-damping hybrid particles in the spraying liquid is 0.3 wt%~0.8 wt%, and the solvent is anhydrous ethanol or methanol.
6. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (3), the spraying pressure is 0.2~0.4 MPa, and the spraying distance is 15~50 cm; the loading of high-damping hybrid particles on the prepreg surface is controlled at 0.25~2.5 mg / cm by controlling the spraying time. 2 .
7. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (4), the hot pressing temperature is 130~250 ℃, the pressure is 0.3~0.7 MPa, and the constant temperature and pressure time is 1~2 h; the fiber prepreg is a resin-based prepreg made of long fibers, and the long fibers include at least one of carbon fiber, glass fiber, aramid fiber, and hybrid fiber.
8. The method for preparing the fiber-reinforced resin-based composite material according to claim 1, characterized in that: The fiber prepreg is a carbon fiber reinforced epoxy resin prepreg, wherein the fiber also includes at least one of glass fiber, aramid fiber, and hybrid fiber; the layup method is any one of symmetrical layup, unidirectional layup, and orthogonal layup.
9. The fiber-reinforced resin-based composite material prepared by the preparation method according to any one of claims 1-8.
10. The application of the fiber-reinforced resin matrix composite material of claim 9 in wind turbine blades, aerospace skins, or transportation structural components.
Citation Information
Patent Citations
A method for preparing aramid nanofibers
CN110055797B
A aramid fiber / carbon nanotube composite reinforced carbon fiber resin prepreg
CN111320841B
A carbon nanotube-reinforced co-cured damping composite material and its preparation method
CN115109281B
Carbon fiber composite material with both interface performance and damping performance and preparation method thereof
CN120535910A
Carbon nanotube reinforced co-curing damping composite material and preparation method thereof
CN115109281A